Libraries as a means for the integration of immigrant populations in Ávila province - Romera Iruela, María Jesús (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Public libraries can be considered as suitable agents and places for the integration of immigrant population. Therefore, services and programs should be developed in order to give an adequate answer to their needs. This article provides some research findings for the information needs of immigrants at Ávila province. These needs are detected from three different perspectives: public libraries, educational centers, and immigrant associations. The data were collected, using ad-hoc questionnaires, in the districts and municipalities with largest immigrant presence. Several intercultural actions directed to the integration of this population are suggested in this research. Thus, amongst others, the need of a Web site with thematic information on the design of cooperative programs on intercultural education between public libraries and scholar libraries, involving both parents of immigrant students and immigrants associations